Climate finance and hunger among non-annex-1 parties: a lens on Sub-Saharan Africa. (29th July 2022) - Doku, Isaac; Phiri, Andrew
Our study seeks to find out whether climate finance is helping reduce hunger among 43 Sub-Saharan Africa (SSA) countries, using system generalised method of moment, pooled OLS and fixed effect models for the period 2006-2018. Three main hunger variables are used in the study; global hunger index (GHI), undernutrition (Under-N) and birthweight (Birth-W). The findings indicate that climate finance exerts a very small effect on all hunger variables. Similarly, other external forms of financing such as foreign direct investment and developmental aid are found to exert little effect on hunger. Notably, domestic factors such as social and economic readiness are found to be more significant in reducing hunger levels.